2021
DOI: 10.1093/ije/dyab168.517
|View full text |Cite
|
Sign up to set email alerts
|

228Relationship of pesticide exposure with kidney function in NHANES: lessons from low level chronic exposure

Abstract: Background Exposure to pesticides has been linked to many health outcomes. More recently, chronic kidney disease not related to diabetes or hypertension (CKDu) has been postulated to be related to rural occupational exposures in agricultural workers in several Low to Middle Income Country (LMIC) regions such as Mesoamerica and the Subcontinent. Our study wished to examine the relationship between pesticide exposure and kidney function. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Currently, no available studies have sufficient evidence to establish causality for agrochemical usage as a putative exposure for CKDu. A clear link between agrochemical usage and CKD has been demonstrated in other settings, with a recent review of NHANES data demonstrating an increased risk of kidney disease associated with both acute and chronic pesticide exposure 41 . Many existing studies in Sri Lanka are of limited utility in making conclusions due to possible bias in: timing of sample collection, selection of locations, recall self‐report bias, failure to distinguish between different agrochemical usage, and failure to adequately capture usage of personal protective equipment (PPE).…”
Section: Methods Of Reviewmentioning
confidence: 92%
See 1 more Smart Citation
“…Currently, no available studies have sufficient evidence to establish causality for agrochemical usage as a putative exposure for CKDu. A clear link between agrochemical usage and CKD has been demonstrated in other settings, with a recent review of NHANES data demonstrating an increased risk of kidney disease associated with both acute and chronic pesticide exposure 41 . Many existing studies in Sri Lanka are of limited utility in making conclusions due to possible bias in: timing of sample collection, selection of locations, recall self‐report bias, failure to distinguish between different agrochemical usage, and failure to adequately capture usage of personal protective equipment (PPE).…”
Section: Methods Of Reviewmentioning
confidence: 92%
“…A clear link between agrochemical usage and CKD has been demonstrated in other settings, with a recent review of NHANES data demonstrating an increased risk of kidney disease associated with both acute and chronic pesticide exposure. 41 Many existing studies in Sri Lanka are of limited utility in making conclusions due to possible bias in: timing of sample collection, selection of locations, recall self‐report bias, failure to distinguish between different agrochemical usage, and failure to adequately capture usage of personal protective equipment (PPE). Differences in exposure measurement between studies may have contributed to some case–control and prevalence studies showing a strong association, 23 , 31 , 33 while others have shown a weak or no association.…”
Section: Methods Of Reviewmentioning
confidence: 99%